2010
DOI: 10.1002/elan.201000246
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Differential Pulse Voltammetric Determination of Cd, Zn and Pb Ions in Water Samples Using Stable Carbon‐Based Mercury Thin‐Film Electrode

Abstract: A new carbon-based mercury thin-film electrode consisting of screen-printed carbon on a low temperature co-fired ceramic substrate was made. Ex-situ mercury deposition in a potassium thiocyanate solution was used. This approach an electrode with high long-term stability (> 500 measurement cycles) and reproducibility ( 2 %) for sensitive determination of ultra trace heavy metals, using differential pulse anodic stripping voltammetry. The detection limits were 0.25, 0.08 and 5.5 ng mL À1 for Cd(II), Pb(II), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Depending on the target of analysis, electrode material has to be chosen in order to obtain a good analytical signal. Popular electrode materials are mercury , bismuth , platin , gold , carbon , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the target of analysis, electrode material has to be chosen in order to obtain a good analytical signal. Popular electrode materials are mercury , bismuth , platin , gold , carbon , etc.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, metallic film electrodes are able to produce very intense and sharp anodic stripping voltammetric peaks, which is highly desirable for trace metal determinations. Several metallic films have been used to prepare chemically modified electrodes, such as: Hg 35, 36, Sb 37, 38, Sn 39 and Pb 40 and literature also brings a comparative study between Bi, Hg, Sb and Sn film for Zn 2+ and Cd 2+ determination 41. However, bismuth film electrodes (BiFEs) are by far the most used and the most attractive metallic film electrode for metal ions determination by ASV.…”
Section: Introductionmentioning
confidence: 99%
“…Another commonly used detection tool is voltammetric techniques which have several advantages such as simple, low cost, rapid and simultaneous multi metal determination and speciation of metal ions in a single step [21,22,[28][29][30][31][32][33][34][35]. Generally anodic stripping voltammetric techniques have been used for the determination of Cd(II) and other metal ions due to their high sensitivities.…”
Section: Introductionmentioning
confidence: 99%
“…Generally anodic stripping voltammetric techniques have been used for the determination of Cd(II) and other metal ions due to their high sensitivities. In this context, studies on sensitive Cd(II) determination were reported using various type of modified electrodes such as Hg [28], Bi [29,30], Sb [31] or HgÀ Bi [32] bimetal film deposited electrodes, graphydine modified GCE [33], graphene quantum dots-Nafion modified GCE [34] and Pyridine-2-sulfonic (or carboxylic) acid modified GCE [35]. Although, atomic spectroscopic techniques integrated with MNPs-DSPME have widely been used for the determination of trace metal ions, only a few voltammetric studies have been reported using MNPs-DSPME.…”
Section: Introductionmentioning
confidence: 99%